Implementasi Pembelajaran Eksploratif tentang Konsep dan Proses Fisika pada Dinamika Fenomena Alam Danau Tondano - Rende, Jeane; Tulandi, Djeli Alvi (Charm Sains: Jurnal Pendidikan Fisika, 2022)
The dynamics of the natural phenomenon of Lake Tondano become a source of student learning in understanding physical concepts packaged in innovative learning as an activity by applying the latest learning elements in the 21st century. The purpose of this study is to describe the implementation of exploratory learning about the concepts and processes of physics in the dynamics of the natural phenomenon of Lake Tondano. The method used in this study is a pre-experimental one group pretest-posttest design. The research stage begins with giving a pretest to measure the students' initial abilities, then takes action (treatment) through exploratory learning and the next activity ends by giving a post-test. The research subjects are fourth semester students of the Manado State University Physics Education Study Program for the 2021/2022 academic year who are contracted for the Environmental Physics course. The evaluation results provide information that the average pre-test is 42.95 and the post-test results are 85.42. The average results of the assessment of science process skills are in good criteria (66%-79%). and very good criteria (80%-100%) affective assessment is in very good criteria (80%-100%). Obtaining N-gain scores from each student, there were as many as 10 students in the high N-Gain category with a percentage of 62.6% and as many as 6 students in the medium N-Gain category with a percentage of 36.8%. The result of the average N-Gain percentage of 16 students is 74.9%. The results of the study explain that students' understanding of physics concepts and science skills can be improved through exploratory learning on the natural dynamics phenomenon of Lake Tondano.